МЕТОДИКА ОРГАНІЗАЦІЇ ФОРМУВАЛЬНОГО ОЦІНЮВАННЯ МОЛОДШИХ ШКОЛЯРІВ В УМОВАХ ДИСТАНЦІЙНОГО НАВЧАННЯ - Предик, Аліна Анатоліївна (Чернівецький національний університет імені Юрія Федьковича, 2022)
Тhe article proposes a method of organizing formative assessment of younger school students in the conditions of distance education, educational platforms are presented that will contribute to the successful and high-quality evaluation of younger school students during online learning
METHODS OF ORGANIZING FORMATIVE ASSESSMENT OF YOUNGER SCHOOLCHILDREN IN THE CONDITIONS OF DISTANCE EDUCATION
Keywords: оцінка; оцінювання; формувальне оцінювання; мотивація; методика формувального оцінювання; дистанційне навчання